The prevalence of swallowing dysfunction in children with laryngomalacia: a systematic review. (December 2020) - Jaffal, Hussein; Isaac, Andre; Johannsen, Wendy; Campbell, Sandra; El-Hakim, Hamdy G.
Abstract: Objectives: Laryngomalacia (LM) is commonly diagnosed in infants and children with upper aerodigestive symptoms. In the literature, the focus has been on the respiratory impairment, with fewer studies addressing swallowing dysfunction (SwD). The objective of this study is to systematically review the literature for evidence on the prevalence of SwD in children diagnosed with LM. Methods: A search was conducted on the following databases: OVID Medline, Ovid EMBASE, EBSCO CINAHL, PROSPERO, and Cochrane Library. We included all the studies that reported on children with LM and documented objective swallowing assessment using fiberoptic endoscopic evaluation of swallowing (FEES) or videofluoroscopic swallowing study (VFSS). Two authors independently screened all the studies, assessed the level of evidence in the included studies, and extracted data. Risk of bias assessment and pooled data analysis were performed. Results: The search yielded 512 abstracts. Four studies met the selection criteria representing 425 children. Three studies were retrospective uncontrolled case series and one was a prospective cohort study. In all studies but one, an instrumental assessment of swallowing was selectively performed in patients with clinical indicators of SwD. The pooled estimate (range) of prevalence of SwD was 49% (13.9–90.6%). Conclusion: The literature suggests a high prevalence of SwD in children with LM, however the level of evidence is low and generalizability is poor. The wide range of prevalence figures suggests a significant variability in the threshold and indications to assess swallowing in children with LM. Highlights: Studies on the prevalence of documented swallowing dysfunction (SwD) in children with laryngomalacia (LM) are scarce. Swallowing dysfunction appears to be highly prevalent in children with LM. Based on the current literature, no clear association between LM and SwD can be defined. Silent aspiration appears to be common in children with LM.